Analysis of Teacher Performance in the Mathematics Learning Process at SMP Negeri 2 Bilah Hulu - Mulia Kurnia Sari; Sakinah Ubudiyah Siregar (Budapest International Research and Critics University, 2021)
This study aims to determine the performance of teachers in Junior High School 2 Bilah Hulu. This research uses descriptive research. The population of this study were 5 mathematics teachers at SMP Negeri 2 Bilah Hulu. Saturated sampling was used to take the sample, meaning that all members of the population were sampled. The data collection technique used a questionnaire with a Likert scale technique. The results of data analysis showed mastery of the material with an average of 86.4, the manifestation of creativity with an average of 80.2, utilization of teaching time with an average of 82.6, student understanding with an average of 83.6 and mastery of the class state with an average average 84.4. The overall results of the indicators get an average of 83.96 with good criteria.